Frozen heat - Castle, Richard (Hyperion, 2012)
NYPD Homicide Detective Nikki Heat arrives at her latest crime scene to find an unidentified woman stabbed to death and stuffed inside a suitcase left on a Manhattan street. Nikki is in for a big shock when this new homicide connects to the unsolved murder of her own mother.